Manual of environmental microbiology - Yates, M. V.; Nakatsu, Cindy H.; Miller, Robert V. 1945-; Pillai, Suresh D., 1962- (ASM Press, 2016)
Provides a comprehensive analysis of general methodologies, environmental public health microbiology, microbial ecology, and biodegradation and biotransformation. Serves as the definitive reference for information on microbes in air, water, and soil and their impact on human health and welfare. An essential reference for environmental microbiologists, microbial ecologists, and environmental engineers, and those interested in human diseases, water and wastewater treatment, and biotechnology.
Keywords: Microbial ecology -- Laboratory manuals.; Sanitary microbiology -- Laboratory manuals.; elektronické knihy; electronic books